CONFLICT MANAGEMENT STYLE AND THE RELATION TO OCCUPATIONAL STRESS - Krawczyk, Denyse do Amaral; Rocha, Vilma Inutuka Pereira; de Almeida, Rogério José (Seven Editora, 2025)
This article aims to analyze associated factors and the correlation between conflict management style and occupational stress of workers at a public hospital that is a reference in rehabilitation and readaptation. This is a cross-sectional and analytical study, using a sociodemographic and occupational questionnaire, the Work Stress Scale (TSS) and the Rahim Organizational Conflict Inventory II (ROCI-II) to assess conflict management styles. The sample consisted of 205 participants, predominantly in care functions (61%). The most prevalent conflict management style was Integration, and less frequent, Dominant. The analysis of occupational variables revealed a direct correlation with higher levels of stress among employees dissatisfied with professional performance, with communication conflicts, and with less time of service in the institution, with time working in the health area from 1 to 5 years, who considered the work environment bad, or who reported frustration with work. In addition, the Dominant style of conflict management was associated with higher levels of stress. DOI: https://doi.org/10.56238/sevened2024.041-013